Давньоруська Желянь (з історії київських околиць) - Мовчан, І.І.; Писаренко, Ю.Г. (Археологія, 1994)
За матеріалами писемних і археологічних джерел розкривається роль місцевості Желянь в історії давнього Києва. Местность Желянь упоминается письменными источниками в связи с военными действиями вокруг Киева в 1093—1167 гг. Анализ приводимых летописями топографических сведений позволяет согласиться с ранее сделанными выводами о местоположении урочища к юго-западу от Киева (в районе современного села Жуляны) на пересечении дорог, ведущих в столицу с запада и юга Руси.
В дополнение к имеющимся археологическим подтверждениям стратегической роли этого района публикуются данные раскопок 1971 г. кургана в Жулянах, содержавшего кочевническое погребение, возможно относящееся к одному из походов на Киев.
Военная специфика истории Желяни заставляет вспомнить персонаж «Слова о полку Игореве» — Жлю (Желю), которая, согласно мнению Б. А. Рыбакова, являлась русской валькирией. Очевидно, название местности, связанной с кровопролитной борьбой за Киев — Желянью, может происходить от имени этого славянского божества. Locality Zhetyan is mentioned id written sources in connection with military actions near Kiev in 1093-1167, An analysis of to- pographic data from chronicles permits acknowledging the pre- viously made conclusions on location of a stow to the south-west of Kiev (at a place of modem village Zhulyany) at crossing of roads leading to the city from the west and south of Rus.
To supplement the available archaeological arguments in favor of the strategic role of this region, we represent data of excavations made in 1971 in a barrow in vil. Zhulyany which contained a nomadic burial belonging, probably, to one of campaigns to Kiev.
Military specificity of the history of Zhelyan impels to think of a personage Zhlyu (Zhelyu) from «The Song of Igor’s Campaign», who, in the opinion of B. A, Rybakov, mas Russian Valkyrie. Apparently, the name of Zhelyan, the locality related to bloody battle for Kiev, may originate from the name of this Slavonic deity.